POSSIBILITIES OF DEVELOPING CREATIVITY THROUGH THE STUDY SUBJECT OF GEOMETRIC MODELLING: STUDENTS' POINT OF VIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article is based on an interdisciplinary approach that incorporates research on education and a study subject. An interdisciplinary approach is extremely important in modern higher education when the same object is studied in the context of two or more subjects. It is also the field of engineering education that is currently highly relevant for universities with a technical profile. Lecturers of the subject should consider not only the content of the study subject but also the didactics of higher education and general competences, including creativity competence, which is perceived as a necessity in the workplace of the 21st century. Therefore, the aim of the article is to analyse the possibilities of creativity through the study subject of Geometric Modelling from the point of view of students. This study subject was chosen deliberately since students are learning to work with AutoCad and Blender software. Their goals are to create 3D models, model them, and visualise them. The article discusses the case of the study subject of Geometric Modelling delivered at VILNIUS TECH. Quantitative research was used, involving a survey of first-year students, which included 93 participants from the Multimedia and Computer Design study programme. To explore the competence of creativity, the areas of exploration, generation, creation, and evaluation were identified. Although most students believe that the study subject fosters creative thinking, they do not always perceive the analysed topics or assigned tasks as contributing to their creativity. They treat it more as the ability to learn how to work with the program and master its functions. It appears that this is influenced not only by the specifics of the study programme and the study subject, but also by the nature of first-year studies. The findings further highlight the importance of expanding the interdisciplinary approach in higher education institutions.